Experimental and numerical study of cemented bone-implant interface behavior - D. Kytyr; T. Doktor; O. Jirousek; P. Zlamal; D. Pokorny (Fracture and Structural Integrity)
Although the total hip replacement (THR) is a long-proven method of surgical treatment of diseases and disorders of the human hip, the surgery brings some risk of long-term instability of the joint. The aim of the research was to investigate the cemented bone-implant interface behavior. The main problems (cement layer degradation and bone-cement interface debonding) during physiological loading conditions have been investigated using a custom hip simulator. The experimental setup was designed to allow cyclic loading of the sample of pelvic bone with implanted cemented acetabular component. The hip contact force of required direction and magnitude was applied to the implant using a spherical femoral component head. The most unfavorable activity (downstairs walking) was simulated. The process of damage accumulation in the fixation was monitored by repeated scanning using high resolution micro Computed Tomography (µCT). Use of micro-focus source and large high-resolution flat panel detector allows investigation of structural changes and crack propagation both in the cement layer and the trabecular bone.